In Defense of Madness: The Problem of Disability. Issue 2 (18th August 2018) - Rashed, Mohammed Abouelleil
Abstract: At a time when different groups in society are achieving notable gains in respect and rights, activists in mental health and proponents of mad positive approaches, such as Mad Pride, are coming up against considerable challenges. A particular issue is the commonly held view that madness is inherently disabling and cannot form the grounds for identity or culture. This paper responds to the challenge by developing two bulwarks against the tendency to assume too readily the view that madness is inherently disabling: the first arises from the normative nature of disability judgments, and the second arises from the implications of political activism in terms of being a social subject. In the process of arguing for these two bulwarks, the paper explores the basic structure of the social model of disability in the context of debates on naturalism and normativism, the applicability of the social model to madness, and the difference between physical and mental disabilities in terms of the unintelligibility often attributed to the latter.